How breakthroughs happen: Unearthing the boundary conditions of eco-friendly deliberate practice and eco-innovation performance - Yin-shi Jin; Asia Sohail; Shahid Iqbal; Tehreem Fatima; Arslan Ayub (PLoS ONE, 2025)
Surprisingly innovation process based on deliberate practice has rarely been unearthed that might explore the boundary conditions of the eco-friendly deliberate practice and eco-innovation performance relationship. Anchored on the organizational support theory and the social cognitive, the current study seeks to investigate the impacts of perceived organizational support (POS) and developmental leadership (DL) on eco-innovation performance (EP) through the mediating role of eco-friendly deliberate practice (EDP). In addition, the study explores the boundary effects of employee resilience (ER) on the relationship between EDP and EP. The study collects time-lagged (i.e., “three-wave”) and multisource (i.e., “self-rated and supervisor-rated”) data from 383 respondents working in the service sector organizations in Pakistan. The authors processed data in SmartPLS (v 4.0) to assess the measurement model and the structural model. The study finds that POS and DL have significant positive relationships with EDP. Further, EDP partially mediates the links between POS, DL, and EP. Moreover, ER intervenes the association between EDP and EP such that at high levels of ER, the relationship is stronger and vice versa. Despite growing interest in deliberate practice, the boundary conditions of EDP in the work context are rarely investigated. This is the first study that explores the contextual and individual factors that can underpin the influence of EDP on EP.